PENGARUH SOSIALISASI SOP ALAT PELINDUNG DIRI (APD) TERHADAP PERILAKU PERAWAT RUANG ICU DALAM PENGGUNAAN APD - Fauzia, Neila; Risna, Risna (Jurnal Sains Riset, 2022)
Nurses as health workers can protect themselves from contact with infectious materials or exposure to infectious diseases by having knowledge of the infection process and proper barrier protection. The high number of work accident cases and the high prevalence of infectious diseases are indicators of the importance of nurses applying standard precautions. The purpose of this study was to identify the effect of socializing the use of PPE on the behavior of ICU Nurses in the use of PPE (Handscoon, Mask, Gown). This study uses a pre-experimental design in the form of a one group pretest-posttest design. The research sample of 35 respondents was taken using saturation sampling technique. There is a significant difference between before and after the socialization of PPE SOPs on the behavior of nurses in the use of PPE (Handscoons, Masks, Gowns) both on the 3rd and 6th day observations after the intervention was carried out with a p value of 0.000. Suggestions for hospital management to routinely hold PPE SOP socialization once a month so that the safety behavior of nurses, especially in the use of PPE can be maintained or increased as an effort to prevent nosocomial infections.Keywords: Use of PPE, Nurse Behavior, PPE SOP socialization